The impact of trade liberalization on the production structure of firms: evidence from India - Zacharia, Salma (School of Economics, 2016)
Recent empirical works have looked at the effect of changes in trade policies on the pattern of production of firms in the developed world. In the context of an emerging economy, this paper looks at India's manufacturing firms' data for the period 1989 to 2003 focusing on reallocation of resources across products within a firm. This is done by evaluating the relationship between tariffs and diversification at product level. The model is further estimated to cater for possible differences in the responses to trade liberalization between exporting and non-exporting firms. This study finds that there is no association between low tariffs and specialization by firms in India. However, this analysis shows that exporting firms appear to diversify more than non-exporting firms following a reduction of tariffs.